Effect of consortia of biocontrol agents and organic amendments in confronting collar rot Sclerotium rolfsii Sacc.) disease in brinjal (Solanum melongena L.) for sustainable cultivation - Kalpana , K; Ayyandurai, M; Theradimani, M; Rajangam, J (Plant Science Today, 2025)
Collar rot, caused by S. rolfsii, is a significant threat to brinjal cultivation in Tamil Nadu. The most virulent isolate of S. rolfsii, identified as IS(VIL)-9, exhibited the highest disease incidence (42.4 %) in field surveys and 92.56 % in pathogenicity tests of our previous studies. The Bacillus spp. and Trichoderma spp. exhibited antagonistic activity against S. rolfsii. Aqueous extracts of various oil cakes including neem, pungam, mahua, castor and cotton were prepared and tested for their antifungal efficacy against S. rolfsii. Among the oil cake extracts, neem oil cake (10 %) exhibited the highest inhibition of S. rolfsii growth (81.11 %), followed by mahua oil cake (76.66 %), pungam oil cake (57.77 %), castor oil cake (34.44 %) and cotton oil cake (18.88 %). In addition, a pot culture experiment was conducted to evaluate the effectiveness of combined applications of biocontrol agents and organic amendments against collar rot disease. Ten treatments were tested, including combinations of Bacillus sp., Trichoderma sp. and neem cake. Bacillus sp., Trichoderma sp. and neem oil cake are compatible with one another in the in vitro assay. Among the various integrated treatments, the combined application of both biocontrol agents, Bacillus sp. and Trichoderma sp., with neem cake (T8) reduced the disease incidence to 14.59 %. The control pots with only S. rolfsii inoculation showed a disease incidence of 80.60 %. This study demonstrated that the integrated use of biocontrol agents and organic amendments such as neem cake and oil cake extracts significantly reduces the incidence of collar rot caused by S. rolfsii in brinjal cultivation providing an eco-friendly alternative to chemical control.